THE AESTHETICS OF VIOLENCE AND CONTEMPORARY SLOVENE WAR NOVELS OF THE NEW MILLENNIUM - Rakovec, Ana (Slavia Centralis, 2026)
This article analyzes three contemporary Slovene novels published in the new millennium that address the theme of the Second World War and were written by women from three different (post)war generations. The novels Saga o kovčku by Nedeljka Pirjevec, Da me je strah? by Maruša Krese, and Angel pozabe by Maja Haderlap are based in intimate family stories, which the authors expand into broader social concerns. Through this approach, the novels reveal wartime and postwar propaganda, they question monumental historical truth, and the commitment to ethical and historical memory. They also expose our general human incapacity to learn from historical mistakes. The use of multiperspectivity and lyricized narration highlights the importance of emotional experience in the formation of memory and postmemory, while also portraying the diversity of wartime experiences.